COMPARATIVE STUDY OF THE ACADEMIC PERFORMANCE OF PUBLIC AND PRIVATE PRIMARY SCHOOL PUPILS IN ILA LOCAL ’ GOVERNMENT AREA OF OSUN STATE - Gbadamosi, B. (Sokoto Educational Review, 2020)
The study compared the academic performance of private and public primary school pupils in lla Local Government Area of Osun State. One hundred and twenty pupils consisting of forty pupils each in primaries three, four and five were involved in the study. Stratified sampling technique was employed in the selection of the schools and pupils for study. The instrument used for the study was the results of the Joint State Examination on English Language and Mathematics for primaries three, four and five. The t-test statistics was used to determine the extent of the difference in the performance of pupils. The results of the study revealed that private primary school pupils performed significantly better than their counterparts in public primary schools in both English Language and Mathematics in all the classes investigated.